PENGARUH TEKNIK REFRAMING MELALUI BIMBINGAN KELOMPOK UNTUK MENINGKATKAN KEPERCAYAAN DIRI SISWA DI SMK KESEHATAN PRO SKILL INDONESIA - Meidil Suhadi; Rosmawati Rosmawati; Siska Mardes (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to examine the effect of reframing techniques to increase the confidence of Pro Skill Health Vocational School students in Indonesia. This type of research is a quantitative study with an experimental method using the research design One-Group Pretest-Posttest Design. The measuring instrument used in this study is the self-confidence measurement scale consisting of 50 items before the validity, and after the validity obtained valid items number 38 items with validity of 0.349 and reliability of 0.884. Determination of the subject using purposive sumpling technique, and getting 7 subjects from the Indonesian Pro Skill Health Vocational School students identified as having low self-confidence levels. The data analysis technique used is non-parametric statistical techniques using the Wilcoxon test. The results of the study proved that the research hypothesis was accepted. This is known from "Test Statistics", known as Asymp. Sig. (2-tailed) is 0.018. Because the value of 0.018 is smaller than <0.05, it can be concluded that "Ha is accepted". To that end, it can be concluded that there is a difference in the self-confidence score before and after being given treatment in the form of reframing technique. Based on the calculations that have been made, the 71% Pre-test is in the low category and 29% in the very low category. Post-test was 14% in the very high category, 58% in the high category and 28% in the medium category. Thus Ha is accepted and Ho is rejected. So that it can be concluded that reframing techniques can increase students' confidence in Pro Skill Health Vocational School Indonesia.Key Words: reframing technique, confidence